Activin A increases human trophoblast invasion by upregulating integrin β1 through ALK4. Issue 2 (23rd November 2020) - Zhu, Shiqin; Li, Zeyan; Cui, Linlin; Ban, Yanli; Leung, Peter C. K.; Li, Yan; Ma, Jinlong
Abstract: Activin A promotes human trophoblast invasion during the first trimester of pregnancy and is associated with preeclampsia and pregnancy‐induced hypertension (PE/PIH) in naturally conceived pregnancies. However, whether integrin β1 mediates activin A‐increased trophoblast invasion remains unknown and the evidence is limited regarding the predictive value of activin A for PE/PIH in women receiving in vitro fertilization (IVF) treatment. Here, we studied the role and underlying molecular mechanisms of integrin β1 in activin A‐promoted invasion in immortalized (HTR8/SVneo) and primary human extravillous trophoblast (EVT) cells. A nest case‐control study was designed to investigate the predictive/diagnostic value of activin A in IVF pregnancies. Results showed that integrin β1 expression increased after activin A treatment and knockdown of integrin β1 significantly decreased both basal and activin A‐increased HTR8/SVneo cell invasion. SB431542 (TGF‐β type I receptors inhibitor) abolished activin A‐induced SMAD2/SMAD3 phosphorylation and integrin β1 overexpression. Activin A‐upregulated integrin β1 expression was attenuated after the depletion of ALK4 or SMAD4 in both HTR8/SVneo and primary EVT cells. Furthermore, we found similar first‐trimester activin A levels in IVF patients with or without subsequent PE/PIH. These results reveal that integrin β1 mediates activin A‐promoted trophoblast invasion through ALK4‐activated SMAD2/3‐SMAD4 pathway, and the predictive/diagnostic value of first‐trimester maternal serum activin A for hypertensive disorders of pregnancy might be different in IVF population.